To multiply \(-1 \frac{1}{6}\) by \(-7\), we first convert \(-1 \frac{1}{6}\) into an improper fraction.
-
Convert the mixed number: \[ -1 \frac{1}{6} = -\left(1 \times 6 + 1\right) / 6 = -\frac{7}{6} \]
-
Now multiply by \(-7\): \[ -\frac{7}{6} \times -7 = \frac{7 \times 7}{6} = \frac{49}{6} \]
-
Convert \(\frac{49}{6}\) back into a mixed number:
- Divide 49 by 6:
- \(49 \div 6 = 8\) (with a remainder of 1)
- So, we can express this as: \[ 8 \frac{1}{6} \]
- Divide 49 by 6:
Thus, the product of \(-1 \frac{1}{6}\) and \(-7\) is \(\boxed{8 \frac{1}{6}}\).